Characteristics of sexual attitudes - Grod, Janet V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
This article is devoted to the study of the features of the formation of sexual attitudes. Approaches to understanding the installation, its distinguishing features and characteristics are considered. The definition of the concept of «attitude to sex» is given. Several approaches are considered, in which the process and mechanisms of the formation of attitudes towards sex are substantiated in different ways. Analysed scientific research, revealing the factors that have the most important influence on the formation of sexual attitudes. It has been determined that the sexual attitudes of people are largely formed under the influence of such factors as the cultural and social environment in which they were brought up, the media, their sexual experience, innate personality traits, sexual orientation, body image, which affects on their sexual behaviour. Because there are no universal cultural or social norms about sexuality, society continues to balance between encouraging and restricting sexual activity. However, while there have been notable changes in attitudes around sexuality over the past decades that have led to transformations in social policy and the International Statistical Classification of Diseases and Related Health Problems, old-fashioned and outdated ideas about sex still remain.